Ph-responsive liposomal systems for site-specific pulmonary delivery of anti-tubercular drugs - Nkanga, Christian Isalomboto (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
Tuberculosis (TB) is an infectious disease that has been reported to be the ninth leading cause of death worldwide, even though mostly considered as a poverty related disease. Despite the existence of potent anti-tubercular drugs (ATBDs), such as rifampicin (RIF) and isoniazid (INH), TB remains the major killer among many microbial diseases over the last five years. Although several factors are to be blamed for this deadly status, the most crucial issues encompass both the self-defensiveness of the causative agent (Mycobacterium tuberculosis), including its intra-macrophage location that compromises ATBDs accessibility, and the widespread/off target distribution of ATBDs. The need for novel drug delivery strategies therefore arises to provide selective distribution of ATBDs at the infected site. Among the drug vehicles explored in this field, liposomes have been reported to be the most suitable drug carriers due to their rapid uptake by alveolar macrophages, where M. tuberculosis often resides. Since liposomes experience media of different pH throughout the cell uptake process (endocytosis/phagocytosis), the use of pH change as a stimulus for controlled release looks promising for enhancing intra-macrophage delivery and minimizing premature 'off-target' release of ATBDs. However, the costly status of liposome technology, due to the use of sophisticated procedures and expensive materials (especially for pH-dependent delivery, where special lipids are required), may preclude wider developments of liposomal products, especially for the developing world. This study aimed at investigating liposomal encapsulation of pH-sensitive and fluorescent hydrazone derivatives of INH using crude soybean lecithin, as a cost-effective option for site-specific delivery combined with potential bio-imaging features. Another objective was to explore encapsulation of INH hydrazone derivatives with and without RIF in liposomes using a simple and organic solvent-free preparation method. Initially, INH was coupled with 4-hydroxy-benzaldehyde to yield a conjugate (INH-HB) that was encapsulated in liposomes using film hydration method with acceptable encapsulation efficiency (Ã®), about 89 %. The prepared INH-HB loaded liposomes (IHL) were characterized by means of dynamic light scattering (DLS), transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The release of INH from IHL was evaluated over 12 hours in media of different pH using dialysis. As hypothesized, pH dependent release of INH from IHL was observed with 22, 69, 83 and 100 % release obtained in media of pH 7.4, 6.4, 5.4 and 4.4, respectively. From this experimental trial, further development was undertaken by conjugating INH to a hydrophobic fluorescent tag, zinc (II) phthalocyanine (PC), through hydrazone linkages. The obtained conjugate (PC-INH) was loaded into liposomes (PIL) that were characterized using various spectroscopic techniques, including UV-Vis absorption and energy dispersive X-ray spectroscopy, which suggested the presence of PC-INH within the lipid bilayers. The release study performed in different pH media revealed 22, 41, 97 and 100 % of INH, respectively released at pH 7.4, 6.4, 5.4 and 4.4. This confirmed the potential of pH-triggered drug release from liposomes loaded with hydrazone drug derivatives. In addition, successful encapsulation of PC-INH using crude soybean lecithin inspired a new opening towards development of multimodal liposomes that could achieve controlled drug release with added benefits of image-guided biological tracking. However, the hydrophobic nature of PC-INH requires an effective strategy that could improve its solubility and favour extensive development. In this context, the tetra-substituted structure of PC-INH brought up the hypothesis that cyclodextrin (CD) complexation would facilitate PC-INH encapsulation in liposomes using an organic solvent-free method, called here the "heating method" (HM). Inclusion complexes of PC-INH with various CDs were therefore investigated, with gamma-CD complex (CP) giving the best results. These complexes were prepared in both solution and solid-state and further comprehensively characterized using UV-Vis spectroscopy, magnetic circular dichroism, NMR spectroscopy, diffusion ordered spectroscopy, DSC, XRD and Fourier transform infrared spectroscopy. CP-loaded liposomes prepared using HM exhibited greater Ã® than film hydration liposomes, about 70 % versus 56 %, respectively. The HM-liposomal system (CPL) exhibited potentially useful nano particulate characteristics (i.e. mean particle size 240 nm and Zeta potential "“57 mV), which remained unchanged over 5 weeks of stability study at 4 Â°C, and pH-dependent INH release behaviour alike PIL. Furthermore, CP was co-encapsulated with rifampicin (RIF) in liposomes using HM to investigate the possibility for future combination therapy. 1H-NMR spectroscopy, DSC, XRD and photophysical studies were performed for molecular assessment of the cargo in CP-RIF co-loaded liposomes (CPRL). The mean particle size, Zeta potential and Ã® of CPRL were respectively 594 nm, "“50 mV, 58 % for CP and 86 % for RIF. CPRL exhibited much higher release rates for both INH and RIF at pH 6.4, compared to those tested at pH 7.4. In addition, there was no cytotoxicity on HeLa cells, but attractive lung fibroblasts and epithelial cells uptake and viability. Hence, CPRL are promising for targeted ATBD delivery to alveolar macrophages following pulmonary administration. Overall, the developed pH-responsive liposomal system holds the promise for new openings towards wider developments of multifunctional liposomes for site-specific controlled pulmonary delivery of antimicrobials drugs.
Keywords: Tuberculosis -- Chemotherapy; Lipsomes; Drug carriers (Pharmacy); Rifampin; Hydrogen-ion concentration; Hydrogen-ion concentration -- Physiological effect